Characterization of Nigerian crude oil aliphatics by gas chromatographic analysis - A.A. OIajire; R.A. Oderinde (Bulletin of the Chemical Society of Ethiopia, 1996)
Bull. Chem. Soc. Ethiop. 1996, 10(2), 115-120.